Modeling for realistic prediction in photothermal therapy: Validation using data from real interstitial laser therapy for breast cancer - André Maurente; Ícaro K.A. Lucena; Gabriel A.D. Paiva (Results in Engineering)
Photothermal therapy for cancer treatment involves complex heat transfer processes. While models have been developed, their ability to provide meaningful results for real cases, making the simulation useful for practical applications, has not been the central focus of previous studies. This work focuses on the validation of a computational model developed within the broader context of research aimed at creating a general framework for simulating photothermal therapy. The validation process involves applying the model to simulate a real treatment and comparing the results to reference values outlined in a treatment protocol. The results align closely with these expected outcomes, increasing model reliability. Additionally, the study provides guidance on the selection of optical and thermophysical properties of human tissues, offering a pathway to more accurate simulations.